2018
DOI: 10.1186/s41021-018-0098-z
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of evaluating γH2AX induction in non-clinical drug development

Abstract: γH2AX, the phosphorylated form of a histone variant H2AX at Ser 139, is already widely used as a biomarker to research the fundamental biology of DNA damage and repair and to assess the risk of environmental chemicals, pollutants, radiation, and so on. It is also beginning to be used in the early non-clinical stage of pharmaceutical drug development as an in vitro tool for screening and for mechanistic studies on genotoxicity. Here, we review the available information on γH2AX-based test systems that can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The typical mode of action of most anti-cancer agents is the induction of DNA damage. Nuclear γH 2 AX staining is a marker of DNA damage-induced cellular repair activity and is frequently used as very sensitive marker for the presence of DNA damage, especially DNA double strand breaks [27]. To assess if UFP induces DNA damage, non-immortalized human skin fibroblasts (HDF) and colon cancer cells (HCT-116) were exposed to 100 µg/mL UPF over 24 h. In untreated HDF, only about 10% of cells showed any γH 2 AX foci at all and these cells displayed typically less than four foci.…”
Section: Resultsmentioning
confidence: 99%
“…The typical mode of action of most anti-cancer agents is the induction of DNA damage. Nuclear γH 2 AX staining is a marker of DNA damage-induced cellular repair activity and is frequently used as very sensitive marker for the presence of DNA damage, especially DNA double strand breaks [27]. To assess if UFP induces DNA damage, non-immortalized human skin fibroblasts (HDF) and colon cancer cells (HCT-116) were exposed to 100 µg/mL UPF over 24 h. In untreated HDF, only about 10% of cells showed any γH 2 AX foci at all and these cells displayed typically less than four foci.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in their review, Siddiqui et al 101 mentioned that γH2AX persisted after exposure to IR under treatment with various radiosensitizing drugs, indicating that this sensor could be used to monitor cancer therapy and to tailor cancer treatments. Using anti-γH2AX monoclonal antibodies and immunofluorescence hybridization techniques to visualize γH2AX localization at sites of DNA damage 102,103 , even with a very low dose of IR exposure, γH2AX foci can be visualized as well, but once the DNA damage is repaired, the foci are eliminated 104,105 . Kuo and Yang 106 suggested that γH2AX foci represent DSBs in a 1:1 ratio and can be used as a biomarker for DNA damage 106 .…”
Section: Cellular Dna Damage Sensors and Early Signal Transducers In Response To Irmentioning
confidence: 99%
“…Some of the assays, such as the Vitotox™ assay measuring mutagenicity, the RadarScreen assay measuring clastogenicity, and the comet assay evaluating DNA breaks, have been optimized for medium to high-throughput formats [28][29][30][31]. Compared with these methods, HCS assays provide more insight into the mechanism of action of genotoxic compounds because of their ability to measure multiple parameters (e.g., γH2AX and micronucleus) [32]. In addition, HCS facilitates the filtering out of false positives.…”
Section: Hcs In Genotoxicitymentioning
confidence: 99%